Notes on Burmese spiders formerly attributed to the genus Storena (Zodariidae, Araneae) - Pakawin Dankittipakul (2018)
Studies on the spider fauna of Southeast Asia resulted in a review of five Storena species which were previously described from Burma. These species were misplaced in Storena Walckenaer, 1805, a zodariid genus that is endemic to Australia. Four species are here transferred to Mallinella Strand, 1906: Mallinella suavis (Thorell, 1895) comb. nov., M. exornata (Thorell, 1887) comb. nov., M. fronto (Thorell, 1887) comb. nov., and M. decorata (Thorell, 1885) comb. nov. Mallinella irrorata (Thorell, 1887) belongs to an undescribed genus of the subfamily Zodariinae. This study also gives a complete list of all Storena specimens examined and studied by Thorell which are now deposited in four European museums. Copyright © 2011.